The Effect of Cell Immobilization by Calcium Alginate on Bacterially Induced Calcium Carbonate Precipitation - Mostafa Seifan; Ali Khajeh Samani; Shaun Hewitt; Aydin Berenjian (Fermentation, 2017)
Microbially induced mineral precipitation is recognized as a widespread phenomenon in nature. A diverse range of minerals including carbonate, sulphides, silicates, and phosphates can be produced through biomineralization. Calcium carbonate (CaCO3) is one of the most common substances used in various industries and is mostly extracted by mining. In recent years, production of CaCO3 by bacteria has drawn much attention because it is an environmentally- and health-friendly pathway. Although CaCO3 can be produced by some genera of bacteria through autotrophic and heterotrophic pathways, the possibility of producing CaCO3 in different environmental conditions has remained a challenge to determine. In this study, calcium alginate was proposed as a protective carrier to increase the bacterial tolerance to extreme environmental conditions. The model showed that the highest concentration of CaCO3 is achieved when the bacterial cells are immobilized in the calcium alginate beads fabricated using 1.38% w/v Na-alginate and 0.13 M CaCl2.